Human capital development practices and career success : The moderating role of country development and income inequality - Bagdadli, Silvia; Gianecchini, Martina; Andresen, Maike; Cotton, Rick; Kaše, Robert; Lazarova, Mila; Smale, Adam; Bosak, Janine; Briscoe, Jon P.; Chudzikowski, Katharina; Dello Russo, Silvia; Reichel, Astrid (Wiley, 2021)
Employees can enhance their human capital through participation in organizationally sponsored development activities. However, there is little research on the extent to which the effects of such practices vary depending on national context. Adopting a human capital theory perspective, we hypothesized a positive relationship between human capital development practices experienced in one's career and objective and subjective career success (salary level and perceived financial success, respectively) and tested two country‐level institutional factors (country development and income inequality) as moderators. Results from our multi‐level analyses of a large‐scale sample of over 8800 managers and professionals from 28 countries showed that, as expected, experiencing a larger number of different human capital development practices was associated with higher salary level and greater perceived financial success. The relationship between development practices and salary level was stronger in the case of developed countries and weakly negatively affected for countries with higher income inequality. The relationship between development practices and perceived financial success was weaker for developed countries and unaffected by income inequality. Our research thus identifies boundary conditions to the application of human capital theory in different contexts and contributes to the comparative careers literature by showing that institutional factors affect the outcome of organizationally sponsored development activities.
Keywords: career success; country development; development practices; income inequality; human capital; fi=Henkilöstöjohtaminen|en=Human Resource Management|